Microdebrider-Assisted Turbinoplasty and Submucosal Diathermy for Inferior Turbinate Hypertrophy: A Randomized Clinical Trial - Muhammad Arshad,Ahmad Hassan Ashfaq, M Tayyab Rasheed , Mahwash Khawaja , Muhammad Arshad,Ahmad Hassan Ashfaq, M Tayyab Rasheed , Mahwash Khawaja (Journal of Rawalpindi Medical College, 2020)
Background: Nasal obstruction is a common presenting problem which can lead to symptoms like sleep disturbances, mouth breathing, oral cavity dryness. Hypertrophied inferior turbinate is a common cause of nasal obstruction. Microdebrider assisted turbinoplasty and submucosal diathermy are widely used methods for patients who fail to respond to medical therapy to relieve obstruction. The aim of the study was to compare two methods in terms of relief of nasal obstruction, reduction in sneezing and post-operative complications. Material & Methods: This randomized clinical trial was conducted at ENT Department, Benazir Bhutto Hospital Rawalpindi, Pakistan for one year from 01-03-2018 to 28-02-2019. One hundred and twenty patients were randomized to into either MAT and SMD groups each with 60 patients. Nasal obstruction symptom evaluation score system (NOSE) was used to access relieve from obstruction and sneezing. SPSS 22, online chai square and fisher exact test calculators were used to analyze the data. Results: Two groups were comparable for age and gender. After 3 months of treatment, all patients in MAT group and 51 patients in SMD group were completely relieved from obstruction. At two weeks follow up 37(61.57%) patients in MAT group had grade 0 obstruction compared with 14 (23.33%) in SMD group and this difference was significant (p value .000). at one month follow up 55 (91.67%) patients in MAT while 46 (76.67%) had completely relieved obstruction and this difference was significant ( p value .024). Not all patients showed reduction in sneezing in both groups. 37 patients in MAT and 25 patients in SMD group had completely relieved from sneezing at third month follow up with MAT group showing significantly more patients with sneezing reduced at one month follow up. Crust formation was most seen complication in both groups, more with SMD group at two weeks follow up which responded to treatment alkaline nasal douches and crust removal. Conclusion: MAT gives better in terms of nasal obstruction relieved, reduction in sneezing and less complications than SMD procedure. Keywords: Microdebrider; Diathermy; Turbinates; Nasal obstruction